Location Selection and Design of Wasi River Intake Jayawijaya Regency - Davy I. Robert Jansen; Dewi Ana Rusim; Apolo Safanpo; Firman Setiawan; Alfian Adie Chandra (Jurnal Indonesia Sosial Teknologi, 2024)
The availability of clean water in Wamena City is a target for fulfilling local government development. In the suburbs, a Public Hydrant (HU) in the Sinakma area has been constructed to meet the community's clean water needs. The fulfillment of clean water needs for network distribution has also existed in Wamena City which was built in 2016 sourced from the Walesi River with the construction of a reservoir in the Napua area, but the distribution was disrupted because the Napua Intake was damaged by landslides. However, due to the condition of landslides and logging that are quite a lot in the upstream area, currently the intake does not function and affects the distribution of water in Wamena City. In 2023, an Intake and several reservoirs with the Wasi River water source in Walesi District have also been built, which are expected to meet the city's water needs. But in reality, the building has not been able to meet the needs of clean water because it cannot capture the flow of water properly.